2014
DOI: 10.3109/14767058.2014.906573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxytocin discontinuation during the active phase of labor

Abstract: It is not reasonable to discontinue oxytocin infusion at the beginning of active labor. Nevertheless, for an accurate conclusion expanded investigations are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Despite a huge interest in oxytocin, relatively few studies have been published concerning the duration of oxytocin infusion, and the results are conflicting [10][11][12][13][14][15] (Table S1). In contrast to our results, a shorter 11 or no prolongation of the active phase of labour 12,14 was found in some previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite a huge interest in oxytocin, relatively few studies have been published concerning the duration of oxytocin infusion, and the results are conflicting [10][11][12][13][14][15] (Table S1). In contrast to our results, a shorter 11 or no prolongation of the active phase of labour 12,14 was found in some previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study supports the finding in three previous studies that the active phase is prolonged when oxytocin is discontinued during the active phase of labour. 10,13,15 Girard et al 13 found that the active phase was around 2 hours longer when oxytocin was discontinued, whereas Ozturk et al 15 found only 30 minutes' prolongation. It could be argued that a shorter duration is not necessarily always beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations